PENGARUH PEMBERIAN CABAI (Capsicum frutescens) TERHADAP PENAMPILAN AYAM PEDAGING: THE EFFECTS OF CAPSICUM FRUTESCENT ON BROILER PERFORMANCE - Elfira Kariane Suawa; Thimotius Sraun; Hulda Ramandey (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2010)
The field and laboratory experiment were conducted to know the effects of fertilization and legumes introduction on the quality natural forages at Kebar Valley, regency of Manokwari. The experiment was designed in a Completely Radomized Design with six treatments and three replications. The results showed that fertilizing and adding legumes had significant effects (p<0.01) on increases of forage species, forage nutrients component (dry matter, organic matter, crude protein), forage production ( fresh and dried), in vitro digestibility (dry matter, organic matter, crude protein) and increasing total digestible nutrient (TDN) and metabolism energy (ME). It is concluded that fertilizing and adding legumes have potential positive effect on improvement of natural forages at Kebar valley, Manokwari regency.